A motivação e o overtraining podem predizer a síndrome do Burnout em atletas de futebol profissional nos diferentes períodos da temporada esportiva - Leonardo Henrique Silva Fagundes (2016)
Strategies to improve soccer performance require physical and psychological training skills. High intensity and volume training to maintain the athletic performance an sports season coupled with an extensive competitive calendar can lead to inadequate recovery of professional soccer players. The imbalance between stress and recovery strategies may result in overtraining symptoms and low levels of motivation. This context can ultimately lead to burnout throughout a sport season. Thus, to better understand motivation, overtraining and burnout syndrome in professional soccer players, the aim of this study was to investigate whether motivation and overtraining can predict the burnout syndrome in professional soccer players during a sport season. A professional Brazilian soccer team was monitored during the 2015 season. The data collection was carried out in eight different times with 32 professional male soccer players throughout the season as follows: baseline (1x), preparatory (2x) and competitive (5x) periods. A demographic data questionnaire and the psychometric instruments: Sport Motivation Scale (SMS), Recovery-Stress Questionnaire for Athletes (RESTQ-Sport 76) and Athlete Burnout Questionnaire (ABQ) were administered in reserved places at the training center. To test the internal consistency reliability of the instruments a Cronbach's alpha () analysis was performed. The Shapiro-Wilk test was used to check the sample distribution. Descriptive statistics was used through median and interquartile range (25-75%). Inferential analyses used were performed using nonparametric Spearman and Friedman tests. Multiple linear regressions were performed in an attempt to predict the burnout syndrome at different times throughout the sports season. Data were analyzed using SPSS 20.0 (Statistical Package for Social Science). Were determined for all measures and the significance level was set to p < 0.05. The results showed that the overall values of Cronbach's alpha () were satisfactory for the dimensions of motivation and overtraining ( > 0.70). However, the sport devaluation ( = 0.67) and reduced sense of accomplishment ( = 0.57) dimensions of ABQ presented values of Cronbach's alpha < 0.70 and were excluded from further analyses. The coefficient correlations between psychological constructs: no correlation (0 < 0,20), weak ( 0,20 a < 0,45), moderate ( 0,45 a < 0,70) and stong ( 0,70) at different times of the sports season. The multiple linear regressions analyses indicated that the baseline demotivation was able to predict the total burnout (Adjusted R2 = 0,376) and emotional/physical exhaustion (Adjusted R2 = 0,324) in the preparatory period. The baseline demotivation was able to predict the total burnout (Adjusted R2 = 0,242) and the physical and emotional/physical exhaustion (Adjusted R2 = 0,351) in the competitive period. Demotivation and sport specific stress at preparatory period were able to predict total burnout (Adjusted R2 = 0,622) and emotional/physical exhaustion (Adjusted R2 = 0,688) in the competitive period. These results indicate that the dimensions demotivation and sport specific stress predicts emotional/physical exhaustion and total burnout in professional soccer players. In summary, it is clear that psychological variables are more latent throughout the sports season increasing the predictive power of the burnout syndrome in different periods